Legal Position of BAWASLU in Monitoring and Preventing Money Politics Practice in Election Process - Susilawati Muharram; Nikmatullah Nur; Alamsyah Agit (PT FORMOSA CENDEKIA GLOBAL, 2023)
The role that BAWASLU, Indonesia's body for election oversight, plays in monitoring and preventing the use of money politics during elections is investigated in this article. It emphasizes the relevance of legislation in the accomplishment of justice, equity, and the growth of both society and the economy. BAWASLU is responsible for upholding election rules, maintaining transparency, mediating disputes, and working to minimize the influence of money in politics through various monitoring and education activities. In addition, the article discusses the role that the Regency or Municipal BAWASLU should play in preventing election violations and disputes. In spite of societal norms and a general lack of comprehension, BAWASLU fulfills an extremely important function in maintaining the credibility of election results.